Bank’s Legal Actions on Lending Issue Against the Annulment of Debtor’s Marriage - Andika Persada Putera (Hang Tuah Law Journal, 2019)
The primary function of Indonesia bank as the collector and distributor of people fund in the form of saving and credit account makes them become a financial agent that bridges surplus unit with deficit unit. Generally, credit is classified into two kinds; commercial and consumer credit. It will be affected due to abrogation of debtor settlement. Although the agreement of credit is not immediately nulled, it needs such a legal action as the solution. Three alternative legal action that bank may consider are: asking for credit settlement at one time, making novation, or letting it out as long as the credit installments are regularly paid. Therefore, this study is a juridical-normative research using both statute and conceptual approaches.